Nanopore facilitated monohydrocalcitic amorphous calcium carbonate precipitation. Issue 30 (26th July 2022) - Page, Katharine; Stack, Andrew G.; Chen, Si Athena; Wang, Hsiu-Wen
Abstract : The observation of protocrystalline monohydrocalcitic amorphous calcium carbonate nucleation in small pores under flow conditions has implications for biomineralization and carbon sequestration pathways. Abstract : Predicting the precipitation of solids is important in both natural systems and subsurface energy applications. The factors controlling reaction mechanisms, phase selection and conversion between phases are particularly important. In this contribution the precipitation and growth of an amorphous calcium carbonate species from flowing aqueous solution in a nanoporous controlled pore glass is followed in situ with differential X-ray pair distribution function analysis. It is discovered that the local atomic structure of this phase indicates monohydrocalcite-like pair–pair correlations, yet is functionally amorphous because it lacks long-range structure. The unexpected occurrence of synthetic proto-monohydrocalcite amorphous calcium carbonate, precipitated from a solution undersaturated with respect to published solubilities, suggests that nanopore confinement facilitates formation of an amorphous phase at the expense of more favorable crystalline ones. This result illustrates that confinement and interface effects are physical factors exerting control on mineral nucleation behavior in natural and geological systems.